THE INFLUENCE OF COMMITMENT TO PERFORMANCE THROUGH ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN SHARIA COOPERATIVES IN MEDAN CITY - Ichsan, Reza Nurul (JURNAL DARMA AGUNG, 2023)
The recovery of economic growth by means of Sharia Cooperative Institutions in Medan City is encouraged to improve the quality of human resources in Sharia Cooperatives in Medan City which plays a very dominant role in the operation of Sharia financial institutions, with the success of Islamic cooperative institutions in achieving predetermined goals is highly dependent on the ability of human resources (employees) in carrying out the tasks assigned, based on the above phenomena, the problem in this study is how much influence Organizational Commitment on employee performance through organizational Citezenship Behavior as an Intervening Variable in Sharia Cooperatives in Medan City, this research was conducted using quantitative research methods. The sample amounted to 180 people in this study, namely employees who worked at Sharia Cooperatives in Medan City, the results of this study were 1) There is an influence of the Commitment variable (X) on Employee performance (Y) at Sharia Cooperatives in Medan City, the results of research that have been conducted Organizational commitment has a positive influence on Employee Performance at Sharia Cooperatives in Medan City; 2) There is an influence of the Organizational Commitment variable (X) on Organizational Citizenship Behavior (Z) at Sharia Cooperatives in Medan City, the results of research that have been conducted Organizational Commitment has a positive influence on Organizational Citizenship Behavior at Sharia Cooperatives in Medan City; 3) There is no influence of the Employee Performance variable (Y) on Organizational Citizenship Behavior (Z) at Sharia Cooperatives in Medan City.